Social Actor Representation in Media Narratives of the Israel-Palestine Conflict Post-October 7: A Study of Al Jazeera, USA Today, and The Jakarta Post - Maharani Pambudi, Pricylia; Sartika, Delita; Handayani, Reli (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The media plays a crucial role in shaping public understanding of international conflicts through strategic linguistic choices that can reveal underlying ideological positions. This study aims to analyze how social actors in the Palestine-Israel conflict after October 7, 2023, are represented in the English-language news coverage of Al Jazeera, USA Today, and The Jakarta Post. Using Critical Discourse Analysis with a focus on van Leeuwen's Social Actor Representation framework, the research examined fifteen news articles published between October 2023 and May 2024 to identify patterns of inclusion and exclusion strategies employed by each news outlet. Findings revealed that Al Jazeera actively portrays both Hamas and Israeli forces as primary agents while occasionally depersonalizing individuals through collectivization; USA Today tends to exclude individual Palestinian actors through indeterminate references while representing Israeli actors more often as collective entities; and The Jakarta Post explicitly names key figures from both sides, personalizing the conflict while emphasizing their opposing roles. These varying representation strategies reflect different editorial approaches that influence how responsibility, agency, and legitimacy are attributed in conflict reporting, ultimately shaping public perception and discourse around the complex geopolitical situation.